Species Composition and Ecological Distribution of the Subfamily Cicindelinae Latreille, 1801 (Coleoptera: Carabidae) Based on Voucher Specimens in Sarawak - ISAAC STIA, MARCELLINUS; SAZALI, SITI NURLYDIA; HAZALI, RATNAWATI; ABDUL RAZAK , AHMAD IRFAN; ABU HASAN AIDIL FITRI, FARAH NABILLAH (Borneo Journal of Resource Science and Technology, 2020)
The subfamily Cicindelinae which belongs to the family Carabidae are commonly known as tiger beetles. Despite the recent studies conducted on this taxon, current ecological knowledge on tiger beetles is limited. Thus, this study aimed to provide a current checklist of tiger beetles as well as their species distribution, abundances and habitat preferences in Sarawak based on voucher specimens from Universiti Malaysia Sarawak Insect Reference Collection (UIRC). A total of 76 specimens of tiger beetles were examined in which comprising of seven genera from eight species. The genus Neocollyris was represented with two species, namely Neocollyris (s. str.) ermaginata and Neocollyris (Stenocollyris) sarawakensis macrodera, while the other genera were represented by only one species, respectively. The most abundant species with 64 individuals (84.21%) were represented by Cosmodela aurulenta, followed by Abroscelis tenuipes araneipes and Therates labiatus with three individuals (3.95%) and N. ermaginata with two individuals (2.63%). In this study, there were eight ecological habitats being identified, namely heath forest, limestone forest, littoral forest, mixed dipterocarp forest, oil palm plantation, peat swamp forest, riverine forest and urban area. The data indicates that C. aurulenta being recorded at seven ecological habitats suggesting this species to have a wide distribution capability while species such as A. tenuipes araneipes, Callytron doriai, Cicindela sp., Myriochila (s. str.) specularis brevipennis, N. ermaginata and N. s. macrodera suggesting these species to have a very narrow habitat specialisation. The results of this preliminary study provide evidence on the need to conduct further studies on the ecological aspects of tiger beetles in Sarawak. Keywords: Cicindelinae, ecological distribution, Sarawak, tiger beetles, voucher specimens